Romidepsin enhances the cytotoxicity of fludarabine, clofarabine and busulfan combination in malignant T-cells. (August 2016) - Valdez, Benigno C.; Brammer, Jonathan E.; Li, Yang; Murray, David; Teo, Esmeralda C.; Liu, Yan; Hosing, Chitra; Nieto, Yago; Champlin, Richard E.; Andersson, Borje S.
Graphical abstract: Highlights: Romidepsin is synergistic with fludarabine, clofarabine and busulfan; exposure of cells to these drugs activated apoptosis. Apoptosis correlated with histone modifications and DNA-damage response. ROS increased while GSH and mitochondrial membrane potential decreased. Some pro-survival pathways were inhibited. Drug transporter MRP1 was down-regulated. Abstract: Novel approaches to pre-transplant conditioning are needed to improve treatment of advanced T-cell malignancies. We investigated the synergism of fludarabine (Flu), clofarabine (Clo), busulfan (Bu), and romidepsin (Rom) in T-cell lines and patient-derived cell samples. [Flu + Clo + Bu + Rom] had combination indexes of 0.4–0.5 at ∼50% cytotoxicity in PEER and SUPT1 cells, suggesting synergism. Drug exposure resulted in histone modifications, DNA-damage response (DDR), increased reactive oxygen species (ROS), decreased glutathione (GSH) and mitochondrial membrane (MM) potential, and apoptosis. Similar activation of DDR and apoptosis was observed in patient samples. The PI3K-AKT-mTOR, NFκB, Raf-MEK-ERK, JAK-STAT and Wnt/β-catenin pro-survival pathways were inhibited by the 4-drug combination. The SAPK/JNK stress pathway was activated. A novel finding was the down-regulation of the drug transporter MRP1. We propose the following mechanisms of synergism: Flu, Clo and Rom induce histone modifications and chromatin remodeling, exposing DNA to Bu alkylation; the increased production of ROS, due to drug-mediated stress response and decreased GSH, damages the MM causing leakage of pro-apoptotic factors; down-regulation of MRP1 increases intracellular Bu concentration and exacerbates the DDR; and inhibition of multiple survival pathways. Our results provide the basis for a clinical trial to evaluate [Flu + Clo + Bu + Rom] as part of conditioning regimen for refractory T-cell malignancy patients undergoing stem cell transplantation.